(untitled) (Global Journal of Management and Business Research, 2019)
The objective of this article is to check the symmetric or asymmetric effects of returns on the volatility of stock prices on the BRVM1. This work takes its theoretical basis of Black and Scholes (1973). The data used are secondary sources from the CD ROM financial data BRVM and CD ROM of the World Bank. The methodology we are inspired by Dalmasso (2016) and has its base Black (1976). Our estimates are made with a method of cointegration in panel data. We find the result that equity returns have asymmetric effects on volatility in the BRVM. This reflects the informational asymmetry which is again a result of the inefficiency of emerging stock markets.